2009
DOI: 10.1242/jcs.051813
|View full text |Cite
|
Sign up to set email alerts
|

BLM helicase stimulates the ATPase and chromatin-remodeling activities of RAD54

Abstract: Mutation of BLM helicase results in the autosomal recessive disorder Bloom syndrome (BS). Patients with BS exhibit hyper-recombination and are prone to almost all forms of cancer. BLM can exhibit its anti-recombinogenic function either by dissolution of double Holliday junctions or by disruption of RAD51 nucleofilaments. We have now found that BLM can interact with the pro-recombinogenic protein RAD54 through an internal ten-residue polypeptide stretch in the N-terminal region of the helicase. The N-terminal r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 33 publications
4
43
0
Order By: Relevance
“…1D and data not shown). Excess SCE in BLM-deficient cells has been shown to be recombination dependent (2,3). We found that RAD51 downregulation decreased the frequency of SCEs to wild-type levels in BLM-depleted cells (Fig.…”
Section: Blm Depletion In Hela Cells Reproduces the Cellular Featuresmentioning
confidence: 58%
See 1 more Smart Citation
“…1D and data not shown). Excess SCE in BLM-deficient cells has been shown to be recombination dependent (2,3). We found that RAD51 downregulation decreased the frequency of SCEs to wild-type levels in BLM-depleted cells (Fig.…”
Section: Blm Depletion In Hela Cells Reproduces the Cellular Featuresmentioning
confidence: 58%
“…SCEs are mediated by homologous recombination (HR; refs. [2][3][4]. BLM deficiency is associated with replication abnormalities and an increase in HR (1).…”
Section: Introductionmentioning
confidence: 99%
“…Assuming that the fusion protein (e.g. EGFP-WRN) is spherical, from the scaling above the diffusion coefficient of the fusion protein is estimated by use of the equation: Dfusion protein=MGFPMfusion protein3DGFP where D GFP is 28 μm 2 /s (Shiratori et al 2002; Braga and McNally 2007; Huranová et al 2010; Grierson et al 2012), M GFP is 27 kDa (Braga and McNally 2007; Compton et al 2008; Van Royen et al 2011), M WRN = 165 kDa (Houtsmuller et al 1999; Compton et al 2008; Srivastava et al 2009), and M BLM = 170 kDa (Erickson 2009; Srivastava et al 2009). To account for possible deviations from spherical shape we follow Erickson (2009) and Spiess and Neumeyer (2010) and reduce the theoretically estimated diffusion coefficient by 20 %, corresponding to a shape-correction factor for globular proteins.…”
Section: Methodsmentioning
confidence: 99%
“…Recombinants and siRNA pGEX4T-1 BLM (1-1417) (Srivastava et al, 2009), pGEX4T-1 BLM (1-212), pcDNA3 Flag BLM (gift from Ian Hickson), EGFP-C1 BLM (gift from Nathan Ellis), pGEX4T-1 BLM (191-660), pGEX4T-1 BLM (621-1041), pGEX4T-1 BLM (1001-1417) (Tripathi et al, 2008). pSG5-Jun (gift from Bohdan Wasylyk).…”
Section: Methodsmentioning
confidence: 99%